Warrnambool Exchange Fire — Resilience and Emergency Management - A Gregory, Mark; Scholfield, Kaye; Ahmed, Khandakar; McLaren, Dorothy; Williams, James; Marshall, Helen (Journal of Telecommunications and the Digital Economy, 2020)
Effective emergency management of a disaster at a single point of failure is vital if the effects of the disaster are to be mitigated. The immediate impacts of a disaster highlight stakeholder perspectives. There is no one-size-fits-all solution to every disaster. Nevertheless, analysing features, aftermath, impact and interim services made available after a disaster provide lessons that can be utilised to avert or mitigate the effects of similar events in the future. This paper provides lessons learnt from a fire that occurred in 2012 in the Warrnambool telephone exchange located in Victoria, Australia and proposes a strategy that provides increased network resilience and more effective emergency management once the copper-based core switching in exchanges is progressively replaced by fibre service area modules.